2022
DOI: 10.3389/fpsyg.2022.895371
|View full text |Cite
|
Sign up to set email alerts
|

COVID Academic Pandemic: Techno Stress Faced by Teaching Staff for Online Academic Activities

Abstract: This paper analyzes the impact of the COVID-19 pandemic on the mental health of the teachers, specifically the techno stress arising in them as a result of issues faced by them in the use of technology when they conduct the online academic activities. It aims to assess the major factors related to the online teaching that specifically adds to techno stress on the teachers during the COVID-19 outbreak. Finally, the study aims to provide suggestions to the policymakers and the management of the universities so t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
2
15
0
4
Order By: Relevance
“…During the times of uncertainty like never before, the need to protect and assist family (family demands) and the need to be an effective employee (job demands) at the same time led to a confused workforce. The role stress increased as job demands became more and more ambiguous ( Liyanagunawardena and Williams, 2021 ; Zheng et al, 2022 ). Employees lacked the ability to immediately switch to the online mode due to a declared education emergency ending up with “technostress” among Pakistani faculty members.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the times of uncertainty like never before, the need to protect and assist family (family demands) and the need to be an effective employee (job demands) at the same time led to a confused workforce. The role stress increased as job demands became more and more ambiguous ( Liyanagunawardena and Williams, 2021 ; Zheng et al, 2022 ). Employees lacked the ability to immediately switch to the online mode due to a declared education emergency ending up with “technostress” among Pakistani faculty members.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has wreaked havoc on education systems worldwide, affecting approximately 1.6 billion students in over 200 nations. More than 94% of the world’s student population has been affected by the closure of schools, institutions, and other learning facilities ( Zheng et al, 2022 ). The pandemic has affected the faculty in these educational institutes as much as it has affected students worldwide, resulting in significant changes in every part of personal and professional lives ( Pokhrel and Chhetri, 2021 ; Zheng et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technical infrastructure and support as well as online learning material need to be improved—both for pupils and teachers. This would likely address most of the above-mentioned points as well as the aforementioned techno stress [ 11 ]. Another point is that due to the still ongoing pandemic, there are many infections among teachers and pupils.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that teachers experienced higher levels of stress than other occupational groups, which added to the already high levels of job-related stress, and that their quality of life decreased [ 9 ]. Those who worked remotely, reported more stress than those who taught in-person [ 10 ], which can be explained by the so-called ‘techno stress’, which includes being forced to expand abilities to use technology as well as working without social contacts [ 11 ]. In one study, 76.7% of the participants reported an increase in burnout during the pandemic [ 12 ], and in another, 58% had seriously considered leaving their job [ 13 ].…”
Section: Introductionmentioning
confidence: 99%